Moral education values in the lyrics of Lengger Lanang art songs: A cultural and educational perspective - Astuti, Neri Dwi; Harimi, Abdal Chaqil (Penelitian Ilmu Pengetahuan Sosial, 2025)
Background: Lengger Lanang is a traditional dance art from Banyumas, Indonesia, performed at various cultural and social events, including baritan (ritual ceremonies to ward off disease), celebrations, and communal gatherings. Accompanied by sinden (traditional singers) and musical instruments, Lengger Lanang features songs with deep moral and philosophical messages. This study aims to analyze and describe these moral values to highlight their relevance in everyday life and their role in cultural preservation. Methods: This study employs an ethnographic approach, utilizing interviews, observations, and documentation to collect data. The research focuses on song lyrics performed in the Lengger Lanang art at the Lengger House Studio, Banyumas District. The analysis identifies moral education values within selected songs, including Eling-Eling, Ricik-Ricik, Bendrong Kulon, and Sekar Gadung. Findings: The study reveals that Lengger Lanang song lyrics serve not only as entertainment but also as an educational medium. The moral education values found in the lyrics include: Morality Towards God – Encouraging piety, patience, contentment (qana'ah), remembrance of God (dhikr), and positive thinking (husnudzan) toward divine will, as reflected in Eling-Eling and Sekar Gadung. Morality Towards Fellow Humans – Promoting respect for parents and teachers (Eling-Eling), cooperation and mutual support (Ricik-Ricik), trustworthiness (Bendrong Kulon stanza 2), and avoiding envy and resentment (Bendrong Kulon stanza 8). Conclusions: Lengger Lanang's song lyrics convey moral values that are highly relevant to daily life, offering guidance through expressions of wisdom, satire, and advice. The research emphasizes the importance of preserving and promoting Lengger Lanang as both a cultural heritage and a means of moral education. Novelty/Originality of this Article: This study provides a unique perspective on Lengger Lanang by focusing on its song lyrics as a medium of moral education. While previous research has primarily examined Lengger as a performance art, this study highlights its role in imparting ethical values, reinforcing its cultural and educational significance.